2007
DOI: 10.1017/s1463423607000266
|View full text |Cite
|
Sign up to set email alerts
|

Addressing cannabis use in primary care: GPs' knowledge of cannabis-related harm and current practice

Abstract: Cannabis is the most commonly used illicit drug in the UK. In 2004, it had a considerably higher prevalence rate compared to other drugs: 10.8% compared to 2.0% ecstasy, the second most prevalent drug (Eaton et al., 2005). Although the UK has historically had the highest rates of cannabis use in Europe, the situation has stabilized since the late 1990s, with the UK now having the fourth highest prevalence rate in Europe (Eaton et al., 2005).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 27 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…Consistent with previous research [18,20-22], GPs and nurses identified not having enough skills, patients not being receptive, and not having enough time as common reasons for not engaging in screening and intervention for cannabis use. Not believing that cannabis use is the most important issue was a new common barrier identified in this study.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Consistent with previous research [18,20-22], GPs and nurses identified not having enough skills, patients not being receptive, and not having enough time as common reasons for not engaging in screening and intervention for cannabis use. Not believing that cannabis use is the most important issue was a new common barrier identified in this study.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, three items assessed beliefs regarding role legitimacy—factors related to the appropriateness of a GP or nurse to intervene with someone’s cannabis use [21,25,27,28] and were rated on a Likert scale from 0 ( disagree completely) to 4 ( agree completely) . One item assessed attitudes regarding cannabis use policy ( Cannabis use should be illegal / decriminalized / available for medical use ) [22,29]. Four open-ended items assessed behavior related to screening, intervention, and referral [22,28,30].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations